1990
DOI: 10.1111/j.1600-0447.1990.tb01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality, parental rearing behaviour and parental loss in attempted suicide: a comparative study

Abstract: Thirty psychiatric patients (aged 18-29) who had attempted suicide were compared with 2 matched control groups, one consisting of nonsuicidal psychiatric patients and the other of normal subjects, for personality patterns, parental rearing practices and personal loss before the age of 15. The instruments used were the Eysenck Personality Questionnaire (EPQ), the Lazare-Klerman-Armor Trait Scale (LKAS), the Narcissistic Personality Inventory (NPI) and the Own Memories of Child-Rearing Experiences (EMBU). Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 58 publications
3
34
1
2
Order By: Relevance
“…It was shown in reports by Benjaminsen et al that parental loss as a result of divorce had occurred significantly more often among psychiatric patients (aged: [18][19][20][21][22][23][24][25][26][27][28][29] who had attempted suicide than that among both nonsuicidal psychiatric patients and normals [23]. Results from a study sample of 1,845 students aged 14-20 in Massachusetts reported that respondents from divorced families had higher suicide attempts relative to those from other family structures, whereas intact families had the lowest rate for suicide attempts [31].…”
Section: Stressful Family Life Events As Risk Factors Of Adolescent Smentioning
confidence: 89%
See 1 more Smart Citation
“…It was shown in reports by Benjaminsen et al that parental loss as a result of divorce had occurred significantly more often among psychiatric patients (aged: [18][19][20][21][22][23][24][25][26][27][28][29] who had attempted suicide than that among both nonsuicidal psychiatric patients and normals [23]. Results from a study sample of 1,845 students aged 14-20 in Massachusetts reported that respondents from divorced families had higher suicide attempts relative to those from other family structures, whereas intact families had the lowest rate for suicide attempts [31].…”
Section: Stressful Family Life Events As Risk Factors Of Adolescent Smentioning
confidence: 89%
“…Independent ratings of adolescents' descriptions of their parents suggested that those exhibiting suicide attempts perceived their parent(s) as more likely to use inadequate parental rearing patterns such as physical discipline, less caring, and much control. There is also consistent evidence that suicide attempters had experienced significantly more negative parental rearing factors than normals [23].…”
Section: Stressful Family Life Events As Risk Factors Of Adolescent Smentioning
confidence: 93%
“…Early parental loss is a risk factor for suicide in adolescents and young adults regardless of sex (30,31). One retrospective study (32) demonstrated that early loss, separation, or inadequate child rearing in young men was more strongly associated with death by suicide than with death from car accidents.…”
Section: Risk Factors For Menmentioning
confidence: 99%
“…Several studies have suggested that certain pregnancy outcomes also may be risk factors, with higher rates of postpartum suicide among women who had a stillborn 9 or a spontaneous or therapeutic abortion compared with women who had a live birth. 5 Case-control studies have demonstrated an association between suicide and suicide attempts [10][11][12] and sudden, intense, adverse personal experiences or losses such as the death of a close friend or relative, especially deaths from suicide. Little is known about the risk for a suicide attempt for a mother whose infant had an adverse outcome within the first postpartum year.…”
mentioning
confidence: 98%